Rebels at sea : privateering in the American Revolution - Dolin, Eric Jay (Liveright Publishing Corporation, a division of W. W. Norton & Company, 2022)
"The best-selling author of Black Flags, Blue Waters reclaims the daring freelance sailors who proved essential to the winning of the Revolutionary War. The heroic story of the founding of the U.S. Navy during the Revolution has been told before, yet missing from most maritime histories of America's first war is the ragtag fleet of private vessels, from 20-foot whaleboats to 40-cannon men-of-war, that truly revealed the new nation's character-above all, its ambition and entrepreneurial ethos. In Rebels at Sea, best-selling historian Eric Jay Dolin corrects that significant omission, and contends that privateers, though often seen as profiteers at best and pirates at worst, were in fact critical to the Revolution's outcome. Armed with cannons, swivel guns, muskets, and pikes-as well as government documents granting them the right to seize enemy ships-thousands of privateers tormented the British on the broad Atlantic and in bays and harbors on both sides of the ocean. Abounding with tales of daring maneuvers and deadly encounters, Rebels at Sea presents the American Revolution as we have rarely seen it before"--